Tips for Choosing a Literature Review Method in the Health Field that Matches the Author's Background - T. Iskandar Faisal; Heru Santoso Wahito Nugroho; Sri Utami (Aloha International Journal of Multidisciplinary Advancement (AIJMU), 2022)
Currently, literature review publications are very widespread by researchers, academics and students. Keywords: literature review; health; author’s background